Vigilância socioassistencial e território: qual equação possível? - Leitão, Aline Lopes (2024)
This dissertation discussed the close relationship between social assistance surveillance and the territory. We talk about the important space for producing theoretical-methodological and technical-operative knowledge that belongs to the social work of socio-assistance surveillance, which is only effective if developed from and in the territory, an element already defined as a guideline for the Assistance policy. Social. Throughout the study, we sought to locate the legal frameworks of the Social Assistance Policy that support Social Assistance Surveillance as a function, striving to maintain that the Policy's surveillance function has a breadth of action and that the Social Assistance Surveillance department is the one that will provide materiality and basis to the work carried out, to guarantee social protection and the defense of rights. To this end, we sought to understand the reality of Social Assistance Surveillance in the cities of Jundiaí and São José do Rio Preto, both located in the interior of the State of São Paulo. Based on historical-dialectical materialism, the research was based on the use of qualitative-quantitative methodology, where we carried out a theoretical study on the topic and shared it with the cities studied, through semi-structured interviews to understand the materiality of the social work of Surveillance Social assistance, the limits imposed for the execution of this work, as well as the need for the three functions of the Social Assistance Policy to complement each other to ensure that the objectives set out in the policy are achieved. During the research process, it was possible to verify the contradictions inherent in the process of materializing the social work of Social Assistance Surveillance, highlighting the need to strengthen its intrinsic relationship with the territory as a mediating element in guaranteeing social protection and the defense and guarantee of rights. Furthermore, Social Assistance Surveillance must embrace the qualitative bias in its work process, knowing the territory, and everyday life, as a scale of data, information, and knowledge production. It is necessary to know and (re)know the experiences of families, and the way life circulates in places, to build subsidies so that all the security guaranteed by the Social Assistance Policy can be guaranteed